2021
DOI: 10.3390/jcm10184187
|View full text |Cite
|
Sign up to set email alerts
|

Association of Low Serum Albumin Level with Higher Hepatocellular Carcinoma Recurrence in Patients with Hepatitis B Virus Pre-S2 Mutant after Curative Surgical Resection

Abstract: Hepatocellular carcinoma (HCC) is, globally, one of the most prevalent and deadly human cancers; despite curative surgical resection, its high recurrence rate after surgery remains a large threat, resulting in poor patient survival. The hepatitis B virus (HBV) pre-S2 mutant that harbors deletions spanning the pre-S2 gene segment has emerged as an important oncoprotein for HCC development and a valuable prognostic biomarker for HCC recurrence; however, its relationship with clinicopathological factors is largel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…On another note, our results revealed that albumin levels were significantly lower in AHCC patients. Our results agree with previous studies reporting that lower levels of albumin in HCC patients are associated with higher Child-Pugh cirrhosis score and higher recurrence rates (21) . Our study has also shown that AFP levels were significantly higher in AHCC patients when compared to EHCC patients.…”
Section: Discussionsupporting
confidence: 93%
“…On another note, our results revealed that albumin levels were significantly lower in AHCC patients. Our results agree with previous studies reporting that lower levels of albumin in HCC patients are associated with higher Child-Pugh cirrhosis score and higher recurrence rates (21) . Our study has also shown that AFP levels were significantly higher in AHCC patients when compared to EHCC patients.…”
Section: Discussionsupporting
confidence: 93%
“…However, there is still room for improvement in the prognostic performance of pre-S2 mutant serving as a biomarker for HCC recurrence. Recently, it has been shown that the presence of deletion mutations spanning the pre-S2 gene segment together with low serum albumin level exhibits better prognostic performance for HCC recurrence after curative surgical resection than that of either biomarker alone [71]. In this study, we further identified that patients with pre-S2 mutant in combination with higher levels of PD-L1 expression and Tregs infiltration in tumor tissues were associated with a higher risk of post-operative HCC recurrence than that of patients with either one or two of these three biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the impact of DAAs on HCV-related HCC recurrence remains debatable, the results of anti-hepatitis B virus (HBV) treatment following HCC therapy showed that NAs might potentially inhibit HCC recurrence after curative hepatectomy in patients with HBV-related HCC[ 43 ]. Managing viral conditions and reactivation of viral replication plays a major role in suppressing HCC recurrence, maintaining liver function, and improving survival for HBV-related HCC post-therapy[ 44 ]. After curative therapy, NAs significantly improved recurrence-free survival and OS in HBV-related HCC patients, and entecavir was on par with other NAs, including lamivudine and adefovir, in this regard[ 45 ].…”
Section: Adjuvant Antiviral Treatmentmentioning
confidence: 99%